Establishment and Current Status of Community Seed-Banks - Wubeshet Teshome; Nesru Temam (Journal La Lifesci, 2020)
Farmers were organized and trained on crop conservation and management, seed selection. Farmers were organized by District Cooperative office with collaboration to EBI for legal entities The key supporter of CSB is District Agricultural office, District Administration office, District youth and women office, District trade office, District land administration office university, NGO and district cooperative office. The members of executive committee are elected every three year by members. Twenty four CSBs have been established, and crop conservation associations are organized and 6 CSBs were under establishment. Twenty one crop type were conserved.